Project management office maturity on project success in construction and infrastructure projects - Alizade, R. (Національний технічний університет "Харківський політехнічний інститут", 2026)
Construction and infrastructure projects are characterized by high complexity, long implementation periods, and a high level of uncertainty. Achieving project success in such environments requires not only effective project-level management but also mature organizational mechanisms that support informed decision-making. The Project Management Office (PMO) plays a critical role in this context by ensuring the selection, adaptation, and standardization of project management methodologies. This paper examines the impact of PMO maturity on project success in construction and infrastructure projects. The study is based on the methodology selection approach proposed by I. Kononenko and A. Kharazii and the project portfolio management maturity level selection method developed by I. Kononenko and M. Kpodjedo. The analysis shows that higher PMO maturity enhances project success by enabling systematic methodology selection and strategic alignment across project portfolios.
Keywords: project management; infrastructure projects; construction; organizational mechanisms; selection approach; portfolios